Bridging the gaps: EFL teacher preparation programs A study in Saudi Arabian Context - Al-Abiky, Waleed Brahim (Journal of Educational and Psychological Sciences, 2019)
Although English, as a core school subject in Saudi Arabia, has been around for almost a century now, the EFL teachers' preparation programs in Saudi Arabia still fail to deliver, help or even set a plan for change as the English proficiency for Saudi students in schools and colleges has for long been low. The current study aimed to investigate some, and might be hidden, causes for the low English achievements for students in Saudi Arabia. Qualitative meta-analysis was used in which four faculty members were semi-structurally interviewed. The findings show that, 1) the average score of Saudi students in TOEFL, as an English standardized test, were low and below expectations especially in reading and writing, 2) there is a huge gap between what students in EFL programs learn and the demands of modern teaching, 3) many EFL programs lack adequate teaching courses and practices, 4) lack of interaction and exposure to native speakers is also problematic and caused shortcomings. The study recommends that more serious redemptions needed despite the recent efforts.
Keywords: EFL programs; teacher preparations; English proficiency; Saudi Arabian context